School and Bicultural Factors as Mediators between Immigrant Mothers' Acculturative Stress and Adolescents' Depression in Korea - Yangmi Lim (MDPI AG, 2023)
In Korea, marriages between Korean men and foreign women have surged since the late 1990s, resulting in public interest in the psychosocial adjustment of their children. This study examined the mediating effects of immigrant mothers' school involvement, adolescents' school adjustment, and bicultural acceptance on the relationship between the mothers' acculturative stress and adolescents' depression, as well as whether the structural relationships differed by the sex of adolescents. Data were collected from 1238 dyads of first-grade students (605 boys, 633 girls; age = 12.97 ± 0.35 years) in Korean middle schools and their immigrant mothers (age = 43.52 ± 5.13 years) who participated in the Multicultural Adolescents Panel Study. The structural equation modeling analysis revealed that mothers' acculturative stress was indirectly and positively related to adolescents' depression through (1) the serial mediations of mothers' school involvement and adolescents' school adjustment and (2) the individual mediation of adolescents' school adjustment. Furthermore, the multigroup analysis indicated that the relationships between adolescents' school adjustment and depression and between adolescents' bicultural acceptance and depression significantly differed between male and female adolescents. The study provides directions for schools and communities to increase immigrant mothers' school involvement and to facilitate their children's school adjustment and bicultural acceptance.